Determination of secondary metabolite content of phenolic group from liquid smoke of coconut shell and husk (Cocos nucifera L.) using visible spectrophotometry - Nabilla, Alfira; Daulay, Anny Sartika (Science Midwifery, 2024)
So far, waste in Indonesia has been increasing. One of the types of waste commonly found in the community is coconut shell and husk waste. However, these wastes contain compounds with potential benefits for health systems. One of the beneficial compounds for health is phenolics and flavonoids. This study aims to determine the total phenolic and flavonoid content in liquid smoke from coconut shells and husks of grades 3, 2, and 1. The stages of this research include raw material processing, pyrolysis, distillation, phytochemical screening, and determination of the liquid smoke content from coconut shells and husks of grades 1, 2, and 3 using visible spectrophotometry. The results showed that the liquid smoke from coconut shells and husks contained flavonoids, tannins, saponins, triterpenoids/steroids, and glycosides. The determination of flavonoid and total phenolic content was carried out by determining the maximum wavelength of quercetin and gallic acid and calculating the total flavonoid and phenolic content using UV-Vis spectrophotometry. The results of determining the total flavonoid content in liquid smoke from coconut shells and husks of grades 1, 2, and 3 were 0.0720±0.828; 0.08975±0; 0.3002±0.00166 mgQE/mL and 0.04393±0; 0.05336±0; 0.52776±0 mgQE/mL. The results of determining the total phenolic content in liquid smoke from coconut shells and husks of grades 1, 2, and 3 were 13.425±0.0447; 14.3583±5.1691; 19.4416±0.1084 mgGAE/mL and 17.016±0.0423; 18.40±0; 18.9083±0.0423 mgGAE/mL. The highest phenolic and flavonoid content was found in the grade 3 liquid smoke, while the lowest content was found in the grade 1 liquid smoke.